LA INFLUENCIA DE LAS REDES SOCIALES EN LA COMUNICACIÓN DEL GRUPO FAMILIAR DE LOS ESTUDIANTES QUE CURSAN EL SEGUNDO AÑO DE BACHILLERATO DE LA UNIDAD EDUCATIVA FISCOMISIONAL “NUESTRA SEÑORA DEL ROSARIO” DEL CANTÓN CATAMAYO, PERIODO 2018-2019 Y LA INTERVENCIÓN DEL TRABAJADOR SOCIAL - Cañar Calderón, Tania Jacqueline (2019)
The present research work called The influence of social networks in the communication of the family group of students who attend the second year of the Baccalaureate of the Fissional Educational Unit "Our Lady of the Rosary" of the Canton Catamayo, period 2018-2019 and the Intervention of the Social Worker, highlights the main findings that respond to the objectives set out in the research where the influence of social networks Facebook and WhatsApp in the communication of the family group is determined, the main causes and consequences that are related due to the Little communication with their parents and siblings means that time is limited to interact with their children, and get involved in activities they do; that is why the ability of young people to interact with other people through social networks is shown many of the times are misused. The consequences generated by the inappropriate use of social networks is the low academic performance, due to the carelessness that young people have for being connected to these platforms for a long time that informs them of news and events that happen in these media, giving reason for existence of conflicts within the family group directly destabilizing the assertive communication in the home, since they neglect their obligations in the home and in the educational environment. Communication in the family group is a determining factor for this social problem that is generated in the educational context. For this reason, it is considered important to establish an intervention proposal with a focus on social work that allows strengthening family communication, so that ICTs do not adversely affect the lives of students. 5 The methodology used for the elaboration of the investigation was the method of the abstract to the concrete which consists of three levels, the external level with its sensitive and information phases that allowed to obtain a broad notion about the object of study and to support theoretical and scientifically research; the conceptual level and its phases of participant research and determination facilitated the approach with those involved to learn about the problem, it was also possible to collect information through the survey and then perform the respective analyzes; The rational logic level with its phases of elaboration of action and execution models in this phase proceeded to propose alternative solutions to reduce the problems that affect the educational trilogy. Likewise, techniques and instruments were used; observation, surveys addressed to 41 students and 41 parents, structured interviews to 6 teacher tutors and 3 professionals of the DECE, field notebook and questionnaires that allowed the collection of information of the object of study, to continue with the processing of information through tabulation and data analysis. As an alternative to this problem it is very important to highlight the participation of the Social Worker in orientation and training for the safe and responsible use of online social networks, through a proposal of social intervention, which allows to strengthen assertive communication, values, principles and on the rules of coexistence within the educational institution and in the family group, in such a way that parents have greater knowledge about prevention strategies and know how to guide their children on time.